2017
DOI: 10.16965/ijar.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

Whatsapp-Assisted Learning of Anatomy as an Adjuvant to Traditional Class-Room Learning: Achievements and Prospect

Abstract: Introduction: WhatsApp is one of the most popular tool of mass media communication besides Facebook and twitter. We all agree a good communication is essential between the teacher and student for a healthy academic environment in every discipline and it is must in Anatomy because of immenseness of this basic science as well as its exposure to the students in a short span. To ease this burden and to facilitate the teaching learning outcome we incorporated WhatsApp shared learning as an adjuvant to class-room te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…Similarly, Kurundawade and Kavale (2018: 198) argue thus: "collaborative learning activities have helped in evolving as a better learner through collaboration". Rajiv et al, (2017) affirm that 78% of the respondents, the learning capabilities of WhatsApp group while 89% of the participants advocated that WhatsApp group should be adopted as an adjunct to classroom teaching regarding ubiquitous availability and collaborative learning. Bouhnik and Deshen (2014) in an Israeli University showed that teachers who initiated WhatsApp groups with their high school students achieved four goals: communicating with students, grooming a positive atmosphere and a sense of belonging in the class, creating a dialogue and using and sharing a learning platform.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Similarly, Kurundawade and Kavale (2018: 198) argue thus: "collaborative learning activities have helped in evolving as a better learner through collaboration". Rajiv et al, (2017) affirm that 78% of the respondents, the learning capabilities of WhatsApp group while 89% of the participants advocated that WhatsApp group should be adopted as an adjunct to classroom teaching regarding ubiquitous availability and collaborative learning. Bouhnik and Deshen (2014) in an Israeli University showed that teachers who initiated WhatsApp groups with their high school students achieved four goals: communicating with students, grooming a positive atmosphere and a sense of belonging in the class, creating a dialogue and using and sharing a learning platform.…”
Section: Discussionmentioning
confidence: 72%
“…Hamad (2017) found that there was no discipline in the group; participant post irrelevant contents. Similarly, Rajiv et al (2017) conclude that challenges experienced by users of WhatsApp include deviation and distraction, non-availability of web service, the low dedication of some student, time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…In another study [30], 75% of the first year medical students gave positive review for M-learning and 54% stated that lectures if succeeded by relevant clinical questions or images over WhatsApp group steer analytical thinking. Also, 79% of the students felt that M-Learning helped with better and quicker knowledge sharing as well as group-discussion to come to a conclusion for better understanding [30]. Table 1: Pre-requisites for an effective m-learning environment.…”
Section: Discussionmentioning
confidence: 98%
“…Even though WhatsApp has been shown to be an exciting new method of sharing subject content, 14 this platform has its own limitations. Through this method, one cannot ascertain whether student has really concentrated on the various components of the images by zooming and panning.…”
Section: Discussionmentioning
confidence: 99%